Exploratory Longitudinal Analysis of the Circulating CHIT1 Activity in Pediatric Patients with Obesity - Ioana Țaranu; Nicoleta Răcătăianu; Cristina Drugan; Cristina-Sorina Cătană; Andreea-Manuela Mirea; Diana Miclea; Sorana D. Bolboacă (MDPI AG, 2023)
Macrophage activation and cytokine release play a pivotal role in inflammation-mediated metabolic disturbances in obesity. The proinflammatory macrophage secretes human chitotriosidase (CHIT1). The expression of the CHIT1 in visceral adipose tissue is associated with cytokine production. Our study aimed to assess whether the CHIT1 circulating activity, as a macrophage activation indicator, reflects the change of the adiposity level and the insulin resistance (IR) in children with obesity. We longitudinally (median follow-up period of 7 months; IQR [5 to 8.5] and {2 to 13} months) evaluated the CHIT1 circulating activity, the adiposity level (waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WtHR), and body mass index (BMI)-for-age z score), and two surrogate markers of IR (Homeostatic Model Assessment for Insulin Resistance, HOMA-IR and the triglycerides-to-high density lipoprotein cholesterol ratio, TG/HDLc) in 29 pediatric patients (16 girls and 13 boys) with obesity. We found a significant reduction in CHIT1 circulating activity (Wilcoxon test, p = 0.015) and a decrease in TG/HDLc at the follow-up evaluation (Wilcoxon test, p < 0.001). Indicators of adiposity were positively correlated with HOMA-IR at baseline, among which WC was the sole indicator associated with HOMA-IR (Spearman's rank correlation coefficients, p < 0.05) at follow-up. Human chitotriosidase has the potential to be a valuable measure of the progression of subclinical inflammation in children with obesity. Subclinical inflammation, as expressed by the circulating CHIT1 activity, progresses independently of the abdominal adiposity, as measured by the clinical indicators, and is associated with a change in insulin resistance.